"Don't be so Harsh": Influence Tactics, Support Transactions, and Relationship Satisfaction. (October 2022) - George-Levi, Sivan; Laslo-Roth, Roni
The current study examined the association between both partners' perceptions of the other partner's use of influence tactics during conflicts (harsh vs. soft) and both partners' relationship satisfaction. Using a dyadic approach, the mediating role of support transactions (i.e., given and received support) was also examined. One-hundred and thirteen couples filled out questionnaires regarding partners' use of influence tactics, received and given support, and relationship satisfaction. Results indicated one partner effect; namely, women's received support was found to be a mediator between women's perception of their partners' use of harsh tactics and both partners' satisfaction. There was only one actor mediation effect of given support and that was observed among women alone; namely, given support mediated the association between harsh tactics and women's relationship satisfaction. Gender and support transaction may play an important role in explaining the link between harsh tactics and relationship satisfaction.